Program Pengasuhan Positif untuk Meningkatkan Keterampilan Mindful Parenting Orangtua Remaja - Pathah Pajar Mubarok (Psympathic : Jurnal Ilmiah Psikologi, 2016)
Deal with children in adolescence stage, parents often showing impatience behavior, unable to control him/herself, complaining when faced with difficulties in parenting and do not listen attentively toward child’s problems. This study aimed to determine the effectiveness of mindful parenting program to improve parenting skills in a positive way. The research method used a quasi-experimental design with measurement technique was Interpersonal Mindfulness in Parenting Scale. The subjects were 28 parents of students of class VII SMPN 15 Bandung. The results showed that the effect of mindful parenting programs has improved significantly on three skills in aspect of positive parenting included listening attentively, emotional awareness of self and children, and self-regulation in the parenting relationship. But for the other two aspects, namely acceptance of self and children without judgment, and the love of self and children the results are less significant.